Social Media Is The Fifth Pillar Of Our Society (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Social media create a virtual word. It means Media is an  instrument on communication, like a newspaper, TV or a  radio, so social media would be a social instrument of  communication. Really social media play a very crucial  role in social media world. We see variety of people on new  media world. We have freedom to categories them,  freedom to pick up and choose them as our friend, as we  do in our real life. But there is a big difference; we do not  actually meet them. Nevertheless, these virtual people  provide us with the platform where we can, without any  hesitation, share our feelings, which otherwise we would  not have discussed face to face. Social media is a 5th pillar,  a potent one, which through the help of technology helps in  the creation and dissemination of information. More ever,  in today's fast new media world, we have paucity of time;  these social media communication tools furnish us with  flexibility of time. It describes websites that allow users to  share content, media, etc. The social media study  comprised a sample of 250 respondents from Delhi-NCR  (including 130 from the NCR region of Delhi), Based upon  the opinions and beliefs of the public, as revealed by the  study. The methodology used in the research work is  convenience sampling. The data has been collected  personally with the help of a well structured and non disguised questionnaire. Common examples are the  popular social networking sites like Friendster, Facebook,  MySpace, Digg, Twitter, YouTube, photo-bucket, flicker  and Wikipedia etc. But these communication tools have  profoundly changed our lives and how we interact with one  another and the world around us.
Keywords: Social networking sites; brand; communication; strategy; social media